Peningkatkan Kemampuan Berpikir Kreatif Peserta Didik Kelas VIII SMPN 18 Makassar melalui Penerapan Media Interaktif ClassPoint dengan Model Discovery Learning (Studi pada Materi Sistem Ekskresi) - Nurhayani H. Muhiddin; Sitti Saenab; Mutia Alfiyanti Muhiddin; Ima Nur Hadisah Ilham (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to determine 1) the level of creative thinking ability of class VIII students of SMPN 18 Makassar before and after the application of ClassPoint interactive media with the Discovery Learning model. 2) increasing the creative thinking skills of class VIII students of SMPN 18 Makassar through the application of ClassPoint interactive media with the Discovery Learning model 3) There is a significant increase in the average value of creative thinking skills after applying ClassPoint interactive media with the Discovery Learning model. This type of research is experimental research (experimental research) using the Pre-Experimental Design. The treatment is the application of ClassPoint Interactive media with the Discovery Learning model in the experimental class. The research population was all class VIII students at SMPN 18 Makassar for the academic year 2022/2023 which consisted of 10 classes with a total of 300 students. The research sample was determined by Purposive Sampling Technique so that class VIII8 was assigned with a total of 30 students. The instrument used in the study was a test instrument in the form of essay questions containing indicators of the ability to think creatively as many as 10 items. Data collection was carried out by giving a Pretest and Posttest. Data were analyzed with descriptive statistics and inferential statistics. The results of the descriptive statistical analysis of students' creative thinking abilities before application (pretest) were in the very less creative category with a value of 12.40 and after the application of ClassPoint interactive media with the Discovery Learning model (posttest) were in the moderately creative category with a value of 55.60. The increase in students' creative thinking skills is in the medium category with an N-Gain of 0.49. The results of inferential statistical analysis show that there is a significant increase in the average value of creative thinking skills after the application of ClassPoint interactive media with the Discovery Learning model.